2023
DOI: 10.33621/jdsr.v5i1.130
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Algorithmic Risks

Abstract: Algorithmic selection is omnipresent in various domains of our online everyday lives: it ranks our search results, curates our social media news feeds, or recommends videos to watch and music to listen to. This widespread application of algorithmic selection on the internet can be associated with risks like feeling surveilled (S), feeling exposed to distorted information (D), or feeling like one is using the internet too excessively (O). One way in which internet users can cope with such algorithmic risks is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…In addition, studies focusing on adolescents reveal an association between a higher level of digital skills and online opportunities (Livingstone et al, 2023). Also, more generally, a person's skill level is relevant for the application of privacy protection strategies (Büchi et al, 2017) and for coping with algorithmic risks (Kappeler et al, 2023), both of which may lead to fewer negative consequences of internet use. Still, the differences in outcomes of internet use and the role that digital skills play remain understudied (Scheerder et al, 2017).…”
Section: Associations With Digital Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies focusing on adolescents reveal an association between a higher level of digital skills and online opportunities (Livingstone et al, 2023). Also, more generally, a person's skill level is relevant for the application of privacy protection strategies (Büchi et al, 2017) and for coping with algorithmic risks (Kappeler et al, 2023), both of which may lead to fewer negative consequences of internet use. Still, the differences in outcomes of internet use and the role that digital skills play remain understudied (Scheerder et al, 2017).…”
Section: Associations With Digital Skillsmentioning
confidence: 99%
“…The effective use of new innovative services, like for instance voice assistants, requires specific digital skills (Gruber et al, 2021). Moreover, they are needed for protecting one's privacy online (Büchi et al, 2017) or for coping with algorithmic risks (Kappeler et al, 2023). In addition, theoretical approaches have suggested that digital skills are an important factor that is associated with the inclusion in the information society (see e.g., Hargittai & Micheli, 2019;Ragnedda, 2020;van Dijk, 2020).…”
Section: Introductionmentioning
confidence: 99%